Differences in specificity, development time and virulence between two acanthocephalan parasites, infecting two cryptic species of Gammarus fossarum - Bauer, Alexandre; Develay Nguyen, Lucie; Motreuil, Sébastien; Teixeira, Maria; Debrosse, Nelly; Rigaud, Thierry (Peer Community Journal)

(untitled)
Multi-host parasites can exploit various host species that differ in abundance and susceptibility to infection, which will contribute unequally to their transmission and fitness. Several species of acanthocephalan manipulative parasites (among which Pomphorhynchus laevis and P. tereticollis) use various amphipod species of the genus Gammarus as intermediate hosts. Many Gammarus pulex and G. fossarum cryptic lineages are living in sympatry in European rivers, questioning the spectrum of intermediate hosts that acanthocephalans can use, and their relative contribution to their life cycles. In this work, the respective roles of parasites species (P. laevis and, for the first time, P. tereticollis) and sympatric host cryptic species (the G. fossarum species complex) were studied experimentally on two traits: host susceptibility to infection and parasite virulence. Differences were found, both in terms of infectivity and virulence, between the cryptic hosts and between the two parasite species. We confirm that these acanthocephalans, previously considered as generalists, show specificities among their sympatric hosts. Differences in field prevalence and susceptibility after experimental exposures were more pronounced between cryptic G. fossarum species for P. tereticollis than for P. laevis. The mortality of infected individuals increased significantly after several weeks of development of both parasite species. P. tereticollis was less virulent than P. laevis, perhaps due to differences in host exploitation, since we evidenced that P. tereticollis had a much slower growth rate.